(untitled) (World Science, 2019)
According to the results of studies, it was found that the term «medical tourism» is used in the specialized literature to define a number of measures related to preserving life, human health, improving the appearance, etc. The term «pharmaceutical tourism» is not defined in the specialized literature. The systematization of modern experience in the functioning of medical tourism in the leading countries of the world indicates that this social phenomenon is a consequence of the implementation of various factors, including socioeconomic ones. One of the most important of these factors is the low availability of medical and pharmaceutical assistance to the population. We defined the concept of «pharmaceutical tourism", determined the forms of its implementation, objects, subjects, and also presented the main functions (medical- pharmaceutical, socio-economic, social, humanistic, market function, stimulating, foreign economic) in the healthcare system in the context of strengthening humanistic principles for the development of society.